Adamantyl thioureas as soluble epoxide hydrolase inhibitors. Issue 13 (15th July 2018) - Burmistrov, Vladimir; Morisseau, Christophe; Pitushkin, Dmitry; Karlov, Dmitry; Fayzullin, Robert R.; Butov, Gennady M.; Hammock, Bruce D.
Graphical abstract: Highlights: Thioureas with adamantane fragment were systematically studied as sEH inhibitors. 45 adamantyl thioureas were synthesized. Difference of activity against human, rat and murine sEH were investigated. Discovered that thioureas are up to 7-fold more soluble than corresponding ureas. Abstract: A series of inhibitors of the soluble epoxide hydrolase (sEH) containing one or two thiourea groups has been developed. Inhibition potency of the described compounds ranges from 50 μM to 7.2 nM. 1, 7-(Heptamethylene)bis[(adamant-1-yl)thiourea] (6f ) was found to be the most potent sEH inhibitor, among the thioureas tested. The inhibitory activity of the thioureas against the human sEH is closer to the value of activity against rat sEH rather than murine sEH. While being less active, thioureas are up to 7-fold more soluble than ureas, which makes them more bioavailable and thus promising as sEH inhibitors.